A new species of Phaedranassa (Amaryllidaceae) from Ecuador - Minga, Danilo; Ulloa Ulloa, Carmen; Oleas, Nora; Verdugo, Adolfo (Phytotaxa, 2015)
Phaedranassa Herbert (1845: misc. 16) is a small genus of bulbous, terrestrial geophytes comprising some eleven species, eight endemic to Ecuador, three known from Colombia, and one from Costa Rica (Meerow 1990). Most of the species are narrow endemics known from few collections. All but one of the species known from Ecuador are considered to be under some threat (IUCN, 2014) because of their restricted distribution and threatened habitat where they occur. Five of them are regarded as Endangered and one as Vulnerable (Oleas 2011). Here we describe a distinctive new species in this genus. Despite its occurrence on cliffs along roads, the species has remained unnoticed by previous floristic explorers.